PENGARUH AROMATERAPI PEPPERMINTT TERHADAP MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I DI KLINIK HJ. NIRMALA PASAR III KRAKATAU KECAMATAN MEDAN TIMUR - Tarigan Sibero, Jitasari; Sartika, Dewi; Siregar, Afrahul Padilah (Universitas Prima Indonesia, 2023)
Background: pregnancy is a physiological condition that begins with intrauterine fetal growth and development and begins from conception to delivery. The period of pregnancy can occur in crisis conditions that require psychological and physiological adaptation of the mother. One of the changes that occur in pregnant women in the first trimester is nausea and vomiting which usually occurs in the morning but can occur at any time even at night. Nausea and vomiting occur in 60% -80% of primigravidas and 40% -60% of multigravidas. Objective: this study was to determine the effect of peppermintt aromatherapy on nausea and vomiting in first trimester pregnant women at the Hj Nirmala Clinic. Method: this type of research is a quasi experimental study using the One Group Pre-post Test Design approach. This research was conducted in September 2021. The sample in this study was 10 people. This statistical test analysis uses the Wilcoxon Sign Rank Test. Results: This study used a statistical test, obtained a p-value of 0.002 <0.05, so that there is an effect of peppermintt aromatherapy on nausea and vomiting in first trimester pregnant women at the Hj Nirmala Clinic. Conclusio: Research shows that there is a significant effect between peppermintt aromatherapy on nausea and vomiting in first trimester pregnant women. It is hoped that it can increase promotive and preventive efforts, especially regarding antenatal care. Efforts that can be made include non-pharmacological therapy to reduce nausea and vomiting in first trimester pregnant women, one way that pregnant women can reduce nausea and vomiting is by inhaling peppermintt aromatherapy.